Type 2 diabetes in young adults in Central Auckland: demography and complications. Issue 1 (3rd January 2018) - Beig, Junaid; Khanolkar, Manish; Cundy, Tim
Abstract: Background: Type 2 diabetes (T2D) in young adults is associated with a high risk of diabetes complications. Aims: To investigated the demography and the emergence of complications of young adults with T2D in the central Auckland region where there has been substantial immigration. Methods: In total, 310 young adults with T2D (<40 years) were registered with the Auckland Diabetes Centre in 2015. We documented demographic, anthropometric and metabolic variables and prevalence and the emergence of complications. Results: Three demographic groups accounted for 243 participants (78%): 135 (44%) were migrants of Asian or Pacific Island origin, diagnosed a median 9 years after migration at a mean age of 28 ± 6 years; 88 (29%) were New Zealand‐born Pāsifika descent, with a high prevalence of morbid obesity and 37 (12%) had major mental illness or intellectual disability. At diagnosis, the median HbA1c was 80 mmol/mol, and in 28%, it was ≥100 mmol/mol. A median 6 years after diagnosis, 56% had some degree of retinopathy, with the prevalence related both to the duration of diabetes and glycaemic control ( P = 0.001). Forty‐four percent of subjects had abnormal albuminuria at diagnosis (12% with macroalbuminuria). Increased albuminuria was strongly associated with obesity ( P = 0.002). The development of CKD stages 4–5 was related both to the severity of retinopathy and degree of albuminuria at diagnosis ( P = 0.0001). Major cardiovascular events were related to the severity of retinopathy at diagnosis ( P = 0.0001). Conclusions: New migrants, New Zealand‐born Pāsifika and patients with mental illness or an intellectual disability comprise the bulk of young onset T2D. The disease is aggressive, and by the age of 40, patients are already developing advanced complications.